The effect of in-season, high-intensity interval training in soccer players - Dupont, G.; Akakpo, K.; Berthoin, S. (The Journal of Strength and Conditioning Research, 2004)
The effects of in-season, high-intensity interval training on professional male soccer players' running performances were investigated. Twenty-two subjects participated in 2 consecutive training periods of 10 weeks. The first period was considered a control period and was compared with a period where 2 high-intensity interval training exercises were included in the usual training program. Intermittent runs consisted of 12-15 runs lasting 15 seconds at 120% of maximal aerobic speed alternated with 15 seconds of rest. Sprint repetitions consisted of 12-15 all-out 40-m runs alternated with 30 seconds of rest. Results from the high-intensity interval training have shown that maximal aerobic speed was improved (+8.1 ± 3.1%; p < 0.001) and that the time of the 40-m sprint was decreased (-3.5 ± 1.5%; p < 0.001), whereas no change in either parameters were observed during the control period. This study shows that improvements in physical qualities can be made during the in-season period.